ECOLOGIA DE Pleurodema diplolister (Peters, 1870) NUMA ÁREA DE CAATINGA NA ZONA RURAL DO MUNICÍPIO DE PARANATAMA-PE - Tenório, José Cleiton Souza; Lima, Emanuel dos santos; Lima, Diego Santos de; Ferreira, Ivson Leon Rodrigues; Araújo, Marina de Sá Leitão Câmara de (Revista Nordestina de Zoologia, 2017)
The present work aims to know some aspects of the ecology and adaptive processes that the species, P. diplolister, developed in the Caatinga biome. During the period from November 2015 to April 2016, a total of 33 specimens of the species referred to were collected from Pit fall traps mounted in 'Y' shaped complexes. The biometric data served as a source for the analyzes of the test X2, Relative Growth and the environmental relation through the spearman coefficient. An allometry was observed in relation to the relative growth, indicating equal development of the variables. The correlation between abundance and environmental factors was low. The present work assists in the knowledge of the biology of the P. diplolister species, besides providing a better knowledge of the species in the Caatinga biome